Entrepreneurship Opportunities after Military Career: Practice in Central and Eastern versus Western Europe - Rasa Smaliukienė (Entrepreneurial Business and Economics Review)
This paper seeks to contribute to the discussion devoted to entrepreneurship of a specific profession group – early retired servicemen. The aim of the paper is to provide a composition of existing practices of entrepreneurship skills development of early retired servicemen in EU member countries and evaluate the differences between Central and Eastern Europe (CEE) and Western Europe (WE) practice. The results indicate the lack of entrepreneurship development policies for early retired servicemen, while service in military often provides highly specific competencies that can be adapted as transferable expertise and knowledge for entrepreneurship.